Why every leader needs to worry about toxic culture : pinpointing the elements of toxic culture in an organization can help leaders focus on addressing the issues that lead employees to disengage and quit - Sull, Donald; Sull, Charles; Cipolli, William; Brighenti, Caio (MIT Sloan Management Review, 2022)
New research based on MIT SMR's Culture 500 and employees' Glassdoor ratings of their employers identifies the five most common elements of toxic workplace cultures as disrespectful, noninclusive, unethical, cutthroat, and abusive. The authors discuss how unhealthy work environments negatively affect both employees and their employers and how organizations stand to benefit when they identify and address toxic elements in their cultures.